Developing an electronic surprise question to predict end-of-life prognosis in a prospective cohort study of acute hospital admissions - Baldev Singh; Nisha Kumari-Dewat; Adam Ryder; Vijay Klaire; Hannah Jennens; Kamran Ahmed; Mona Sidhu; Ananth Viswanath; Emma Parry (Clinical Medicine)
Objective: Determining the accuracy of a method calculating the Gold Standards Framework Surprise Question (GSFSQ) equivalent end-of-life prognosis amongst hospital inpatients. Design: A prospective cohort study with regression calculated 1-year mortality probability. Probability cut points triaged unknown prognosis into the GSFSQ equivalent ‘Yes’ or ‘No’ survival categories (> or < 1-year respectively), with subsidiary classification of ‘No’. Prediction was tested against prospective mortality. Setting: An acute NHS hospital. Participants: 18,838 acute medical admissions. Interventions: Allocation of mortality probability by binary logistic regression model (X2=6,650.2, p<0.001, r2 = 0.43) and stepwise algorithmic risk-stratification. Main outcome measure: Prospective mortality at 1-year. Results: End-of-life prognosis was unknown in 67.9%. The algorithm’s prognosis allocation (100% vs baseline 32.1%) yielded cohorts of GSFSQ-Yes 15,264 (81%), GSFSQ-No Green 1,771 (9.4%) and GSFSQ-No Amber or Red 1,803 (9.6%). There were 5,043 (26.8%) deaths at 1-year. In Cox’s survival, model allocated cohorts were discrete for mortality (GSFSQ-Yes 16.4% v GSFSQ-No 71.0% (p<0.001). For the GSFSQ-No classification, the mortality odds ratio was 12.4 (11.4–13.5) (p<0.001) vs GSFSQ-Yes (c-statistic 0.72 (0.70–0.73), p<0.001; accuracy, positive and negative predictive values 81.2%, 83.6%, 83.6%, respectively). Had the tool been utilised at the time of admission, the potential to reduce possibly avoidable subsequent hospital admissions, death-in-hospital and bed days was significant (p<0.001). Conclusion: This study is unique in methodology with prospectively evidenced outcomes. The model algorithm allocated GSFSQ equivalent EOL prognosis universally to a cohort of acutely admitted patients with statistical accuracy validated against prospective mortality outcomes.